A Comparative Study on Buying Behavior of Customers towards Branded Apparel over Non Branded Apparel with Special Reference to Raipur City (International Journal of Scientific Research and Management (IJSRM), 2017)
Indian markets have been very popular in fashion and it has been same in Raipur city. This study is conducted to find out the consumer’s buying behavior towards branded apparels over non-branded apparels in this city. The purpose is also to study how consumer behavior for apparel is influenced by factors like monthly income, gender and peer influence .The survey conducted in Raipur city shows that the consumers prefer shopping mostly with their friends and family members. They are influenced by their choices of their friends, family members, celebrities, magazines etc. Quality, comfort, brand are the main criteria’s which impact their buying behavior towards branded apparels over non branded apparels The study shows there are different attributes which attracts customers towards branded apparels over non branded apparels